The Effect of Work Ethic and Work Discipline on Performance of Elementary School Teachers of Muhammadiyah in Tegal Regency - Rahmadita, Adinda; Wibowo, Ugung DA; Rahardjo, Pambudi; Wulandari, Dyah Astorini (PSIMPHONI, 2022)
This study investigates the impact of work ethic and work discipline on the performance of Muhammadiyah elementary school teachers in Tegal City. A quantitative research design was employed, utilizing regression analysis to assess the relationships between these variables. The sample comprised 65 teachers from Muhammadiyah elementary schools in Tegal Regency. Data were collected using a structured questionnaire. The analysis revealed that both work ethic and work discipline have a significant positive effect on teachers' performance. Specifically, work ethic enhances teacher performance, work discipline contributes positively to performance, and together, they substantially influence teachers' effectiveness.To further improve teacher performance, it is recommended that educational institutions implement programs designed to strengthen work ethics and enhance work discipline among teachers. Additionally, future research could explore other factors that may interact with work ethic and discipline to affect teacher performance, including institutional support and professional development opportunities.